Increasing the radiation safety of nuclear power plants using the method of controlling the tightness of fuel elements - Mamontov, О.; Nevliudov, I.; Stytsenko, T.; Belikov, A.; Tokarieva, О. (Вопросы атомной науки и техники, 2022)
The problem of monitoring the tightness of fuel elements at the stage of their manufacture to improve the radiation safety of nuclear power plants is considered. A vibration method is proposed for non-destructive testing of the tightness of cylindrical fuel rods. The method makes it possible to perform accelerated testing of a batch of fuel rods and remove samples with gross leakage under conditions of mass production. A description of the method is given, a mathematical model of free vibrations of a fuel element is developed. The time dependences of the pressure and the period of free oscillations of the fuel element were obtained by calculation. The assessment of the influence of the inhomogeneity of the fuel element structure on the test result is carried out. Inhomogeneity causes an error in measuring the oscillation period up to 1%, which can lead to a false result. Three-dimensional plots were constructed, reflecting the main form of free vibrations of a homogeneous and inhomogeneous section of a fuel element. On the basis of the performed assessment, recommendations were given for conducting fuel rod tightness control, excluding a false result. Розглянуто проблему контролю герметичності твелів на етапі їх виготовлення для підвищення радіаційної безпеки АЕС. Запропоновано вібраційний метод неруйнівного контролю герметичності твелів циліндричної форми. Метод дозволяє виконати прискорений контроль партії твелів і видалити зразки з грубими порушеннями герметичності в умовах серійного виробництва. Наведено опис методу, розроблена математична модель вільних коливань твела. Розрахунковим шляхом отримані залежності тиску і періоду вільних коливань твела від часу. Виконано оцінку впливу неоднорідності конструкції твела на результат контролю. Неоднорідність викликає похибку вимірювання періоду коливань до 1%, що може привести до помилкового результату. Побудовано тривимірні графіки, що відображають основну форму вільних коливань однорідної і неоднорідної ділянок твела. На підставі виконаної оцінки дані рекомендації з проведення контролю герметичності твелів, які виключають помилковий результат. Рассмотрена проблема контроля герметичности твэлов на этапе их изготовления для повышения радиационной безопасности АЭС. Предложен вибрационный метод неразрушающего контроля герметичности твэлов цилиндрической формы. Метод позволяет выполнить ускоренный контроль партии твэлов и удалить образцы с грубыми нарушениями герметичности в условиях серийного производства. Представлено описание метода, разработана математическая модель свободных колебаний твэла. Расчетным путем получены зависимости давления и периода свободных колебаний от времени. Выполнена оценка влияния неоднородности конструкции твэла на результат контроля. Неоднородность вызывает погрешность измерения периода колебаний до 1%, что может привести к ошибочному результату. Построены трехмерные графики, отражающие основную форму свободных колебаний однородного и неоднородного участков твэла. На основании выполненной оценки даны рекомендации по проведению контроля герметичности твэлов, исключающих ложный результат.